Ethics of Artificial Intelligence in Islamic Religious Education: The Perspective of the Qur'an, Hadith, and Maqā Sīd al-Sharī'ah in the Era of Society 5.0 - Ahmad Saifuddin Ma’sum; Irmawan Jauhari (Mataram University, 2026)
Development Intelligence Artificial Intelligence (AI) in the era of Society 5.0 has bring change big in the world of education , including Islamic Religious Education (PAI). The presence of AI provides opportunity For increase effectiveness , accessibility , personalization , and innovation learning through various system education digital- based . However , the integration of AI in Islamic education also presents various challenge ethics , such as risk dehumanization , shift spiritual values , algorithmic bias , AI hallucination , uncertainty epistemology of religion, as well as threat to participant data privacy and security education . Research This aim For analyze ethics the use of AI in Islamic Religious Education is based on perspective of the Qur'an, Hadith , and maqā ṣ id al- syarī' ah . Study use approach qualitative with method study bibliography and analysis descriptive-thematic . Data obtained through technique documentation from primary sources in the form of the Qur'an and Hadith as well as source secondary consisting of top 20 articles journal scientific , books academic and publication scientific publications published over a period of 2022–2026 . The literature was selected based on the criteria of relevance to the themes of AI, Islamic Religious Education, Society 5.0, digital ethics, and maqā ṣ id al-syarī'ah. Data analysis was carried out through the stages of open coding , axial coding , and selective coding to identify the main themes of the research. The results of the study indicate that Islamic ethical principles such as sincere intention, tabayyun, etiquette towards knowledge and teachers, and the practice of knowledge are important foundations in the use of AI in Islamic Religious Education. This study also found that maqā ṣ id al-syarī'ah which includes the protection of religion, intellect, life, descendants, and property can be a normative framework in the development and evaluation of AI technology. The main contribution of this study is the formulation of an AI ethics model that integrates the principles of Islamic learning ethics with maqā ṣ id al-syarī'ah as a conceptual foundation for the development of Islamic Religious Education in the era of Society 5.0. Therefore, AI needs to be positioned as a learning support tool that strengthens humanistic, spiritual, and moral values, not as a substitute for the role of educators.